2005
DOI: 10.1016/j.jsgi.2005.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Feto-maternal Bone Remodeling in Normal Pregnancy and Preeclampsia

Abstract: Increased bone resorption and decreased bone formation occur in preeclampsia in both mother and fetus, being more pronounced in the latter. The increased osteoclastic activity in preeclampsia may be attributed to increased RANKL induced by increased interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-alpha), and transforming growth factor beta2 (TGF-beta2) production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The increased osteoclastic activity in preeclamptic women may possibly be attributed to an increase in RANKL (which, however, was not measured [24] ). Nevertheless, our study, comprising not only preeclamptic but also women with pregnancy-induced hypertension, did not demonstrate any differences in serum OPG and sRANKL concentrations between the study groups.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The increased osteoclastic activity in preeclamptic women may possibly be attributed to an increase in RANKL (which, however, was not measured [24] ). Nevertheless, our study, comprising not only preeclamptic but also women with pregnancy-induced hypertension, did not demonstrate any differences in serum OPG and sRANKL concentrations between the study groups.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, in pregnancies complicated with preeclampsia, increased bone resorption has been reported in both mothers and fetuses [24,25] . The increased osteoclastic activity in preeclamptic women may possibly be attributed to an increase in RANKL (which, however, was not measured [24] ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, maternal plasma IL-6 levels are elevated in women with PE [71,72], and increasing IL-6 levels can stimulate production of agonistic auto-antibodies to the angiotensin II type 1 receptor. The source of increasing IL-6 in maternal plasma remains unknown [73,74], but several studies found that the placenta is not the source.…”
Section: Discussionmentioning
confidence: 99%
“…The urinary DPD and serum osteocalcin levels were higher in preeclampsia than in normotensive pregnancy 36 . The OC and PICP levels were significantly decreased in severe preeclampsia, whereas the NTx level was significantly increased compared to the corresponding levels of controls 37 . The ICTP and PICP levels were significantly increased in women with preeclampsia compared with the normal pregnant controls 7 …”
Section: Discussionmentioning
confidence: 96%